2004
DOI: 10.1523/jneurosci.4970-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Environments Enhance the Induction and Maintenance of Long-Term Potentiation in the Dentate Gyrus

Abstract: The induction of long-term potentiation (LTP) in the hippocampal formation can be modulated by different behavioral states. However, few studies have addressed modulation of LTP during behavioral states in which the animal is likely acquiring new information. Here, we demonstrate that both the induction and the longevity of LTP in the dentate gyrus are enhanced when LTP is induced during the initial exploration of a novel environment. These effects are independent from locomotor activity, changes in brain temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
93
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 75 publications
11
93
3
Order By: Relevance
“…The VTA dopamine fibers are unique among biogenic amines innervating the hippocampus in that they participate in a rewarddetection system that promotes LTP and learning (4,35,36). During exploratory behaviors, when gamma-frequency activity occurs in the DG and DGCs fire at high rates (1,3,(37)(38)(39), the reward salience of an external stimulus is signaled by release of dopamine from VTA projections to the molecular layer of the DG (40).…”
Section: Discussionmentioning
confidence: 99%
“…The VTA dopamine fibers are unique among biogenic amines innervating the hippocampus in that they participate in a rewarddetection system that promotes LTP and learning (4,35,36). During exploratory behaviors, when gamma-frequency activity occurs in the DG and DGCs fire at high rates (1,3,(37)(38)(39), the reward salience of an external stimulus is signaled by release of dopamine from VTA projections to the molecular layer of the DG (40).…”
Section: Discussionmentioning
confidence: 99%
“…Permanent electrodes were implanted as described previously (Villarreal et al, 2002;Davis et al, 2004). Briefly, rats were anesthetized with pentobarbital sodium (Nembutal, 65 mg/kg, Henry Schein, Melville, NY) with supplemental injections (10 mg/kg) to maintain a surgical level of anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Novel environments elicit exploration and theta rhythm, thought to reflect a sustained period over which the animal is acquiring new information (Davis et al, 2004). Novel environments were made from Plexiglas cages identical in size to the home cage (47 ϫ 25 ϫ 20 cm) and included fresh bedding and 4 -5 plastic or metal objects, such as boxes and small toys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novelty modulates various forms of hippocampus-dependent plasticity. Exploration of a novel context can either enhance or impair long-term potentiation in the hippocampus (Xu et al 1998;Abraham et al 2002;Li et al 2003;Straube et al 2003;Davis et al 2004) and can strengthen learning in a variety of hippocampus-dependent tasks (Moncada and Viola 2007;Ballarini et al 2009;Almaguer-Melian et al 2012). A recent study demonstrated that exposure to a novel context can enhance extinction of CFC (de Carvalho Myskiw et al 2013).…”
Section: Discussionmentioning
confidence: 99%